Pilot Study of Breast Cancer Patients with a Long Term Follow up in Erbil-Iraq - M Esmael Najjar , Suhel (Diyala Journal of Medicine, 2020)
Background: Breast cancer remains as the most common malignant neoplasm in females and one of the main life-threatening diseases, this long-term follow-up study under run for patients of carcinoma of the breast. Objective: To gain practical feedbacks from the progression and fates of the patients who had been managed by the standard is previously known international guidelines. Patients and Methods: This retrospective study involved (40) breast cancer cases In Erbil-Iraq for more than 15 years. Checkup tools were clinical examinations, laboratory investigations, and images for recurrence and metastasis. The following parameters had been studied; Age, clinical presentation, histopathological diagnosis, staging and management including surgeries, further adjuvant therapies and survival rates by periodic follow-up both in hospital and home visits. Results: The results of this study showed that the left breast affected more frequently by 2:1 than the right. In 85% of patients, 1st presentations were in the 1-3 months and in stage II. Age's distribution was mainly between 31-60 years. Only 6 (15%) cases showed positive family history. The most common histopathology type was infiltrative ductal carcinoma 27(67.5%) and the prominent grades were (GII and GIII). Molecular based distribution of (Luminal B) was the biggest immunohistochemical type. About 70% of the cases were managed by quadrectomy or simple mastectomy and/or Axillary clearance. By (15) years follow-up (42.5%) cases lived between 5 to 10 years, and another (17.5%) survived above 10 years. No relation found between the cope of patients with her malignancy and course of the disease. Conclusion: In the future, we have to concentrate on middle age and more scientific educations as they are most affected by (IDC) with advanced searching management routes. Older patient’s carcinoma convention was less aggressive than younger, their life expectancy longer after diagnosis and treatment options. In the young group patient's tumor was more aggressive. Anyhow, breast cancer character remained unpredictable for various involved factors complexity and physiological variability of females. Recurrences, metastasis, and survival depend on familial and environmental code factors. Delay diagnosis is still a disaster in this locality that interferes with better results.